The Effects of Fluoride Varnish on Shear Bond Strength and Adhesive Remnant Index of Ceramic Orthodontic Brackets - Hassani Behbahani, Mina; Namdari, Mahshid; Seyedsalehi, Simasadat; Mohsenzade, Hedie; Vazirizadeh, Yasamin; Sedighinia, Maryam; Behnaz, Mohammad (Journal of Dental School, 2024)
Objectives This research sought to assess how fluoride varnish affects the shear bond strength (SBS) and adhesive remnant index (ARI) of ceramic brackets used in orthodontics. Methods Forty-eight freshly extracted premolars were randomly assigned to four groups (N=12 each). Groups 1, 2, and 3 were treated with 5% sodium fluoride varnish 1, 7, and 14 days before ceramic bracket bonding, respectively. Group 4 as the control group received no pretreatment. The SBS of the brackets was measured using a Universal Testing Machine, while the adhesive remnant on the tooth surfaces was assessed based on the ARI. The SBS and ARI were analyzed statistically using one-way ANOVA and Kruskal-Wallis tests, respectively at a significance level of 0.05. Results Group 2 exhibited significantly lower SBS than that of group 1 (P=0.001). Group 1 displayed higher SBS than that of the control group (P=0.016). Additionally, group 3 exhibited greater SBS than group 2 (P=0.020). However, none of the groups showed an SBS lower than the standard value of 6 MPa. Regarding ARI, a significant difference was found only between Groups 1 and 2, with Group 2 showing a higher ARI than Group 1 (P=0.025). Conclusion The application of fluoride varnish at 1, 7, and 14 days prior to bonding ceramic brackets in orthodontics does not decrease SBS and does not significantly affect ARI compared to the control group.